УДОСКОНАЛЕННЯ ЗАСОБІВ ЗАБЕЗПЕЧЕННЯ ЯКОСТІ ЕЛЕКТРОЕНЕРГІЇ В СУДНОВИХ ЕЕС З НАПІВПРОВІДНИКОВИМИ ПРОПУЛЬСИВНИМИ КОМПЛЕКСАМИ - Жук, Д.О.; Жук, О.К.; Козлов, М.О. (Інститут електродинаміки Національної академії наук України, 2024)
Considered are possible directions for improving the means of ensuring the quality of electric power (PQ) in order to increase their efficiency, taking into account the schematic and mode features of integrated ship electric power systems (SEPS) with semiconductor propulsion complexes (SPC). One- and two-link variants of system controlled filter compensation devices (CFCD) designed for simultaneous full compensation of reactive power, as well as significant weakening of harmonic distortions of voltage and current in SEPS with SPC, are proposed and investigated. A modeling approach has been implemented that allows to compare the effect of the proposed CFCD on the integral coefficient of voltage harmonic distortions in systems with different types of input rectifiers as part of the frequency converters (FC) of the SPC, taking into account the possible deviation of the frequency of the ship's network. Ref. 7, fig. 6, table.